PENINGKATAN HASIL BELAJAR MATERI BANGUN DATAR MELALUI MODEL TEAM ASSISTED INDIVIDUALIZATION DI KELAS IV B SD NEGERI 47 KOTA JAMBI - Heni Maladewi (Jurnal Pesona Dasar, 2019)
To be able to learn something well, we need to hear, see, ask questions about it, and discuss itwith others. Not only that, students need to "do it", which is describing something in their ownway, showing examples, trying to practice skills and doing tasks that demand the knowledgethey have gained. This research addressed the question: Is the Team Assisted Individualizationmodel able to improve students’ learning outcomes in mathematics? While the purpose of thisstudy was to find out how far the implementation of the Team Assisted Individualization modelcan improve Mathematics in the topic of Flat Surfaces learning outcomes in class IV B. Thisresearch uses two rounds of action research. Each round consists of four stages, namely:design, activity and observation, reflection, and revision. The target of this study is class IV B.The data obtained are in the form of formative test results, observation sheets of teaching andlearning activities. From the results of the analysis it was found that student learning outcomesexperienced an increase from the first cycle to the second cycle, namely, the first cycle (80.64)and the second cycle (87.09%) The conclusion of this study is that the Team AssistedIndividualization model can have a positive effect on the learning outcomes of Jambi CityElementary School 47 students, and this learning model can be used as an alternative inmathematics learning.Keywords: Cooperative Team Assisted Individualization (TAI) Model, mathematics 26